PENGARUH KUALITAS KEHIDUPAN KERJA DAN MOTIVASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MEDIASI KEPUASAN KERJA (STUDI PADA ANGGOTA POLISI POLDA JAWA TENGAH) - Iswiarto, Erwin; Soliha, Euis (Jurnal Ilmiah Telaah Manajemen, 2019)
The purpose of this study was to examine the effect of work life quality and motivation on Polri member Organizational Citizenship Behavior with moderating variable job satisfaction. This research was conducted in the Central Java Regional Police (Polda), with the sampling technique using the Nonprobability Sampling technique, especially the Convenience Sampling and Judgment Sampling as many as 100 members of the national police as respondents. This study uses multiple regression analysis techniques. The research instrument used in this study fulfills the requirements for validity and reliability. Hypothesis testing results indicate that work life quality and motivation have a positive effect on Organizational Citizenship Behavior, Job Satisfaction significantly is not a factor that mediates the influence of work life quality on Organizational Citizenship Behavior and motivation towards Indonesian Police Citizenship Behavior members. Keywords : Quality of work life, Motivation, Job Satisfaction, and Organizational Citizenship Behavior.